(untitled) (Journal of the College of Basic Education, 2026)
Wrestling is considered one of the essential subjects in the colleges and departments of physical education and sports sciences, due to its global status as an Olympic sport that provides excitement and attraction for its followers. Moreover, it plays a significant role in preparing students mentally, physically, and motorically, given the diversity of its holds and defensive and offensive skills. This requires giving due attention to its learning stages both theoretically and practically. The research problem, as identified through the observations of the researchers, lies in the fact that most instructors do not sufficiently employ modern teaching methods within the field of physical education and sports sciences. This has negatively affected the learning process, which requires continuous diagnosis and analysis to address weaknesses. To tackle this issue, the researcher adopted the experimental method using a one-group design, as it was suitable for the nature of the study. The findings revealed that the use of specific exercises based on the cooperative learning strategy had a positive effect on teaching some wrestling holds to students